THE SYNDROME OF CHRONIC ABDOMINAL ISCHEMIA. A CLINICAL CASE - M. O. Loginov; M. A. Nartaylakov; S. M. Giniyatullin; A. R. Galiakberov (Креативная хирургия и онкология, 2017)
One possible cause of resistant abdominal pain syndrome is a chronic intestinal ischemia caused by varying degrees of occlusion of the mesenteric vessels. Due to the variety of clinical manifestations, just noticeable their specificity and lack of awareness of general practitioners timely diagnosis of the syndrome of chronic abdominal ischemia is difficult. The method of choice of surgical treatment is percutaneous transluminal angioplasty and stenting of the arteries.